The Effect Of Financial Condition, Company Growth, And Company Size On Going Concern Opinion Acceptance - Tubagus Muhammad Resky Adiningrat; Muhammad Yusuf; Ayatulloh Michael Musyaffi (Research Trend in Technology and Management, 2024)
This study aims to investigate the effect of financial condition, company growth, and company size on going-concern opinion acceptance. This research will use secondary data from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The research sample taken is a transportasion and logistic company selected by purposive sampling. 26 companies were chosen as the samples of this study. The method used is logistic regression analysis. The result of this research is that financial condition had a negative influence on the audit going concern opinion acceptance and the other company growth and company size do not have influence to the going concern opinion.